A mixed-methods investigation into elite alpine skiers` coping strategies during competition - Cundale, M.; Arnold, R.; Lambdon, J.; Moore, L. J. (International Journal of Sport Psychology, 2024)
In elite sport, athletes often encounter potentially stressful events, leading them to engage in various coping strategies. To date, these coping strategies have yet to be explored among elite skiers. Thus, this study investigated: (1) elite skiers` coping strategy usage, and whether it differed based on sex, nationality, and competitive level, and (2) the links between coping strategy usage and trait stress appraisals, perceived performance, and psychological well-being. Following a mixed-method design, 44 elite skiers (21 female; Mage = 22 years, SD = 4) completed an online survey assessing coping strategies, trait stress appraisals, performance, and wellbeing. Semi-structured interviews were also undertaken with seven skiers (Mage = 25 years, SD = 7). Results found differences based on sex, competitive level, and nationality, and highlighted some novel coping strategies (e.g., focus on inspiring others). Task-oriented coping, alongside momentary distraction-oriented coping, were associated with challenge appraisals and better performance and well-being among the elite skiers.